2008
DOI: 10.1002/fam.977
|View full text |Cite
|
Sign up to set email alerts
|

Mass and size distribution of firebrands generated from burning Korean pine (Pinus koraiensis) trees

Abstract: SUMMARYThe present study reports on a series of real-scale fire experiments that were performed to determine the mass and size distribution of firebrands generated from Korean Pine (Pinus koraiensis), a common conifer species indigenous to China, Japan, and Korea. The experiments were performed at the Building Research Institute in Tsukuba, Japan. The total tree height was fixed at 4.0 m and tree moisture content was varied to examine the influence that this parameter has on the mass and size distribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 10 publications
2
56
0
Order By: Relevance
“…For all tests, Douglas-fir wood pieces machined to dimensions of 7.9 mm (H) by 7.9 mm (W) by 12.7 mm (L) were used to produce firebrands. The same-size wood pieces were used to feed the bench-scale continuous Firebrand Generator in past studies and have been shown to be commensurate with sizes measured from full-scale burning trees, as well size distributions obtained from actual WUI fires [22,28].…”
Section: Experimental Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all tests, Douglas-fir wood pieces machined to dimensions of 7.9 mm (H) by 7.9 mm (W) by 12.7 mm (L) were used to produce firebrands. The same-size wood pieces were used to feed the bench-scale continuous Firebrand Generator in past studies and have been shown to be commensurate with sizes measured from full-scale burning trees, as well size distributions obtained from actual WUI fires [22,28].…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…Interestingly, post-fire damage studies have suggested for some time that firebrands are a significant cause of structure ignition in WUI fires, yet for over 40 years, firebrand studies have focused on understanding how far firebrands fly, known as spotting distance [10][11][12][13][14][15][16][17][18][19][20]. Few studies have examined firebrand generation [21][22][23] and the ultimate ignition of materials by firebrands [24][25][26][27]. For these reasons, the prior firebrand studies are of limited help in designing firebrand-resistant structures.…”
Section: Introductionmentioning
confidence: 99%
“…Manzello et al [5] have shown that the firebrands produced using these filtering and ignition procedures generate firebrands with mass up to 0.2 g and surface area up to 1000 mm 2 . This is within the range of firebrands generated from burning conifer species (Douglas-Fir and Korean Pine Trees) [8][9].…”
Section: Nist Firebrand Generator (Nist Dragon)mentioning
confidence: 66%
“…While firebrands have been studied for some time, most of these studies have been focused on how far firebrands fly [4][5][6][7][8][9][10][11][12][13][14]. Unfortunately, very few studies have been performed regarding firebrand generation [15][16][17] and the ultimate ignition of materials by firebrands [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently Manzello et al [17,[22][23][24][25] developed an experimental apparatus, known as the NIST Firebrand Generator (NIST Dragon), to investigate ignition vulnerabilities of structures to firebrand showers. The NIST Firebrand Generator is able to generate a controlled and repeatable size and mass distribution of glowing firebrands.…”
Section: Introductionmentioning
confidence: 99%